Who loses and who wins in the ride-hailing era? A case study of Austin, Texas. (May 2022) - Li, Shengxiao(Alex); Zhai, Wei; Jiao, Junfeng; Wang, Chao (Kenneth)
Abstract: Ride-hailing has redefined vehicle access and has the potential to reduce travel difficulties for transit-poor areas and people with poor access to private and public transportation resources. Due to the lack of data, current studies lack a holistic understanding of how transportation resources serve different social groups and places in the ride-hailing era in low-density areas. This study uses multiple sources of data in Austin, Texas to understand: (1) how ride-hailing usage, transit supply, and vehicle ownership distribute across neighborhoods with different densities, income, and racial and ethnic compositions; (2) who are ride-hailing users among those with and without private vehicles, and how their ride-hailing usage and attitudes towards ride-hailing versus transit differ. Our study has shown that the ride-hailing services have provided residents living in low-income, low-density neighborhoods, and neighborhoods with a majority of Hispanics with an alternative transportation mode. However, residents living in low-density and low-income neighborhoods still use ride-hailing services less frequently than those living in high-density and high-income neighborhoods. The user survey further shows that ride-hailing users without private vehicles tend to be racial and minorities or younger people with higher education attainments. Ride-hailing services provide people with a convenient and safe transportation mode, regardless of their vehicle ownership. Our study shows the importance of ride-hailing in mitigating the social and spatial disparity and the opportunity of integrating ride-hailing and transit in transportation planning in low-density areas. Highlights: This study uses multiple data sources to study neighborhood and individual-level transportatation dirstributions. Frequent ride-hailing usage, dense transit supply, and high share of zero-vehicle owners concentrate in downtown Austin. Ride-hailing services support daily transportation for transport disadvantaged areas and people in Austin. Ride-hailing services have the potential to integrate with public transit systems in low-density areas.